Accessory right hepatic artery and its significance for a surgeon: A case report - Gupta, Niraj; Kumar, Rohit; Verma, Amar; Mohammad, Irshan; Sharma, Heena; Rai, Rahul (Indian Journal of Case Reports, 2024)
Right hepatic artery (RHA) is a branch of the common hepatic artery; however, there are cases documented in the literature showing anatomical variations. Accessory RHA is an incidental finding during hepatobiliary and pancreatic surgery. This artery should be identified, carefully separated, and preserved during these surgeries. We encounter the variation while doing Whipple’s procedure in a 61-year-old patient diagnosed with carcinoma of the head of the pancreas. Intra-operatively, accessory RHA was present which was arising from the superior mesenteric artery. It was identified, carefully separated, and preserved. Variations in the origin of the artery may make it vulnerable to injuries during surgical procedures if due care is not taken.